How to promote local governments collaboration? evidence from carbon reduction in the Yangtze River Delta - Liu, Yue; Cang, Yaodong (Frontiers in Environmental Science, 2025)
China’s central government has proposed a “dual carbon” goal to promote carbon peaking in every province. Collaboration on carbon reduction among local governments is considered an efficient approach to address the carbon emission issues in China. In response, the YRD region implemented the collaborative mechanism and achieved success in carbon reduction. However, there are still some factors that limit the effectiveness of collaboration, such as inconsistencies in priority sectors and goals for carbon reduction. Therefore, comprehensively identifying the factors that influence collaboration would contribute to understanding the reasons for inefficient collaboration, and exploring the relationships among these factors could provide guidance on promoting collaboration. This study presents a structural model and an impact mechanism model for collaboration through grounded theory, cluster analysis and variation coefficient analysis. The results suggest that there are five factors that influence collaboration: Equitable allocation and pressure from monitoring are pressure factors, governance cost and collaborative benefit are state factors, and governance responsibility is the individual factor. The pressure factors could affect collaboration by affecting state factors, while individual factor plays a moderating role between state factors and collaboration. The research findings provide new insights for promoting collaboration on carbon reduction.